An Analysis of Personal Financial Management Practices among First-Year Students at the University of Eswatini: Array - Kwenda, Farai; Sihlongonyane , Silungile (The Journal of Accounting and Management, 2021)
Objectives: This study analysed the personal financial management practices of first-year students at the University of Eswatini (UNESWA). Prior work: Literature on personal finance suggests that university students engage in poor financial management practices and are generally financially illiterate. There are limited studies on personal financial management among university students in particular first-year students. Little is known as to how first-year university students in a developing country like the Kingdom of Eswatini manage their limited financial resources. Therefore, an analysis of the financial conduct of first-year students in this developing country is necessary. Approach: The study analysed four key personal financial management practices: budgeting, spending, saving and investing to determine whether students engage in sound or unsound financial management practices. The study adopted a quantitative research approach and a survey research design. The study utilised primary data collected through self-administered questionnaires to 326 proportionally and randomly sampled students from a population of 1 760 students. Results: The findings indicated that UNESWA first-year students engage in sound financial management practices. The t-test and ANOVA analysis showed that the students’ financial management practices vary significantly with their gender, type of high school they attened and their programme of study. Logistic regression analysis results showed that gender is the only demographic variable predicting financial management practices. Implications : These findings suggest that more financial education campaigns would improve the financial management practices of students. Value: This study contributes to the personal financial management literature by offering evidence on how first-year students in a developing country are managing their limited resources.